Worldwide financial reporting : the development and future of accounting standards - Benston, George J.; Bromwich, Micheal; Litan, Robert E.; Wagenhofer, Alfred (Oxford ; New York : Oxford University Press, 2006)
The book addresses two related challenges:the way in which financial reporting can deal with increasingly comple business transactions and the demand for a single set of high quality international accounting standards.
Includes bibliographical references (p. 307-320) and index.
aia 07/05/13
Loans
Keywords: Accounting - standards; Financial statements